Komunikasi Lingkungan Suku Kajang Ammatoa Dalam Menjaga Hutan - Emil Fatra Fatra; Rusli Rusli (Komunika : Jurnal Ilmiah Komunikasi, 2025)
This study examines the Andingingi Ritual as a medium of cultural communication that reflects the relationship between the Kajang Ammatoa indigenous community in Bulukumba, South Sulawesi, and their environment. The research employs a qualitative method using a case study approach, with data collected through observation, interviews, and documentation of the ritual’s implementation, including its symbolic meanings and ecological roles. Data analysis follows the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. The findings indicate that the Andingingi Ritual functions as a mechanism of ecological communication that fosters environmental awareness through ritual symbols, customary messages (Pappasang), and collective community practices. Each stage of the ritual conveys ethical and ecological messages, such as the obligation to protect forests, preserve water resources, and respect spiritual entities regarded as guardians of nature. From a cultural communication perspective, the ritual strengthens indigenous identity and social cohesion, while from an environmental perspective, the Andingingi Ritual serves as a form of ecological education rooted in local wisdom that supports the preservation of the Kajang customary forest and broader ecological sustainability.